Early motor rehabilitation of children with autism - Khasanova S.M.; Vershinina A.R. (Theory and Practice of Physical Culture, 2023)
А variety of opinions regarding the early start of physical rehabilitation indicate the importance of conducting further research and analyzing the results in order to better understand the impact of motor activity on the psychophysical and social characteristics of children with autism.